Climate reconstruction for the Entre‐Douro‐e‐Minho region (NW Portugal) between AD 1626 and AD 1820: synthesis of viticulture data and foraminiferal evidence. (25th June 2018) - Moreno, João; Fatela, Francisco; Gonçalves, Mário A.; Leorri, Eduardo; Trigo, Ricardo M.; Moreno, Filipa; Gómez‐Navarro, Juan J.; Brázdil, Rudolf; Ferreira, Manuel J.
Abstract : This work presents two novel climate‐related time series for the northwest of Portugal. The first is an AD 1626–1820 triennial‐resolved wine production series, based on the Benedictine accounts from six monasteries of the Entre‐Douro‐e‐Minho (EDM) region. The second, an AD 1654–2010 benthic foraminiferal record from the Caminha salt marsh, located in the lower estuary of the Minho River. The series were analysed together for the common period to outline how both palaeoclimatic proxies respond to the most likely natural environmental drivers of temporal variability, solar forcing included. Singular spectral analysis revealed a common significant multidecadal periodicity agreeing with recognized long‐term changes in solar activity, i.e. the Lower Gleissberg cycle (50–80 years). The application of wavelet analysis allowed the detection of high coherence at this time scale (centred at c . 64 years) between marsh foraminifera and both total solar irradiance and the North Atlantic Oscillation index. This relationship persists throughout the c . AD 1730–1875 period. The continuous wavelet transform results for wine production were inconclusive. As the time‐span analysed is recognized as one of high socio‐economic and political distress, the main human‐driven impacts on wine production, particularly in the two periods of greatly reduced solar activity – the Maunder and Dalton Minima – are reviewed in the light of the available historical records. In addition to a documented climate‐related agricultural crisis in Portugal, damage and losses to wine production may have been triggered by several local and international conflicts in which the country was involved. But to what extent the two influences contributed to the wine production variations observed in the EDM region during both periods remains an open question.